Studies on Physiological and Biochemical Changes in Relation to Seed Viability in Aged Onion Seeds - K Bhanuprakash (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2006)
Rapid loss in viability of onion seeds during seed storage is a major problem. Not much information concerning the physiological and biochemical changes is available. In the present investigations, seeds were aged artificially by exposure to 45°C+75% RH for a period of fifteen days. Samples were collected at three day intervals and physiological and biochemical changes in the aged seeds were compared to those in fresh seeds. Results revealed that ageing affected seed viability and vigour significantly and this effect was more pronounced with increase in duration of exposure to artificial ageing. Marked reduction in germination to an extent of 4,16 and 75% was noticed in three, six and nine day artificially aged (DAA) seeds, respectively, when compared to fresh seeds. Further increase in ageing duration to twelve and fifteen days resulted in total loss of germination. Increase in ageing duration decreased a amylase and dehydrogenase activities but increased peroxidase activity up to nine days of ageing. Lipid peroxidation increased consistently with increase in duration of ageing. At 15 DAA, 26.2% increase in malondialdehyde content over the control was observed. SDS PAGE protein profile and esterase zymograms of aged seeds showed alteration in banding pattern when compared to that of fresh seeds.